STUDY OF C45 ALGORITHM IN PREDICTING NEW EMPLOYEE ACCEPTION - Khoirunsyah Dalimunthe; Zakarias Situmorang (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
Good employee performance is one of the criteria in the company where one has good behavior and can complete the work given to him. But there are some difficulties in knowing the quality of people who have good potential as employees in a company. Therefore, a method or method is needed to identify prospective employees of a company. The C4.5 algorithm can be used to predict and classify prospective employees who have the potential to enter the company by making a decision tree based on existing data and predicting new prospective employees who want to enter the company.